Archive's renewable value: electronic insights in the past record. The biological memory of the ecosystem for the information society - (:unkn) unknown (My University, 1999)
The information recorded for the archival collection of fishes, marries innovation and regional interest. The South-West Atlantic from the then Portuguese Guinea to the South of Portugal has been the research scenario to the Andalusian Marine Science Station of the Spanish Scientific Research Council from 1955. The marine fishes of West Africa are considered, in the archive, under the possibility of envisage the bottom fauna in the area as representing the transition between the Atlanto-Mediterranean and the Tropical faunas. The experimental parameters to check involve analysis of DNA, and molecular phylogenetic relationships between species could be established in the case of Lophius budegassa and Lophius piscatorius. Determining the extent of the effects on wild populations of the introduction of new species could be learned after the Fundulus heteroclitus. Because the capture date is known, an age can be estimated to the fishes. In particular, to age Neoharriotta pinnata, the holotype for this animal. The specimens of Nezumia aequalis, Schedophilus ovalis, and Tachysurus gambensis are enough rare for the application of the entire spectrum of temporal techniques. The discrimination of populations in mixed stock fisheries seems to be regarded with particular authority when examining material without description in the area of the strait of Gibraltar like it is the case of Ptheirichthys linneatus. Determining temporal trends in genetic diversity of managed fish populations and examining the regulatory role of pathogens on historic ecosystems could be offered after a closer analysis of the museum.
Keywords: African Research